Chronicle - Archives of Acoustics, Editorial Board (Archives of Acoustics, 1997)
1. International Symposium on Hydroacoustics and Ultrasonics, 12-16 May 1997, Jurata;2. XLIV Open Seminar on Acoustics, Jastrzębia Góra, 15-18.09.1997;3. Calendar of Meetings and Congresses, Compiled for the International Commission on Acoustics - May 1997.